FREMTRÆDELSES-FORMER: Åndebesættelsen som mimesis og performance - Sjørslev, Inger (Tidsskriftet Antropologi, 1997)
Inger Sjørslev: Forms of Representation. Spirit Possession as Mimesis and Performance The title of the article plays on the literal meaning “stepping forward” of the Danish word “fremstilling” for representation. It analyses the phenomenon of ritual spirit possession as stylistic behavior and a form of communication, and as an embodiment of sociality, in the sense that the possessed incamates forces and sentiments of the whole group. The possessed are not dissociated from themselves as much as they are morethan- themselves in this sense of being - framed by the ritual performance - fetishlike incamations of both positive sentiments of the group, as when possessed by gods, and negative ones, as sometimes when possessed by marginal entities and strangers.